A calibration method based on virtual large planar target for cameras with large FOV. (February 2018) - Yu, Lei; Han, Yangyang; Nie, Hong; Ou, Qiaofeng; Xiong, Bangshu
Abstract: In order to obtain high precision in camera calibration, a target should be large enough to cover the whole field of view (FOV). For cameras with large FOV, using a small target will seriously reduce the precision of calibration. However, using a large target causes many difficulties in making, carrying and employing the large target. In order to solve this problem, a calibration method based on the virtual large planar target (VLPT), which is virtually constructed with multiple small targets (STs), is proposed for cameras with large FOV. In the VLPT-based calibration method, first, the positions and directions of STs are changed several times to obtain a number of calibration images. Secondly, the VLPT of each calibration image is created by finding the virtual point corresponding to the feature points of the STs. Finally, intrinsic and extrinsic parameters of the camera are calculated by using the VLPTs. Experiment results show that the proposed method can not only achieve the similar calibration precision as those employing a large target, but also have good stability in the whole measurement area. Thus, the difficulties to accurately calibrate cameras with large FOV can be perfectly tackled by the proposed method with good operability.